PENGARUH ADVERSITY QUOTIENT TERHADAP RESISTANCE TO ORGANIZATIONAL CHANGE - Astuty, Isthofaina; Bharata, Sriwijaya (Universitas Muhammadiyah Magelang, 2010)
The aims of this research is to examine the influence of adversity quotient to resistance of organizational change. The object of this research is PT Citra Nusantara Energi (PT CNE) with 63 employee of the population. The instrument that used is liner regression sample analysis. The result of analysis showed that adversity quotient give negative influence to resistance of organizational change.